The Long-Run Consequences of Chernobyl: Evidence on Subjective Well-Being, Mental Health and Welfare - Alexander M. Danzer; Natalia Danzer (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper assesses the long-run toll taken by a large-scale technological disaster on welfare, well-being and mental health. We estimate the causal effect of the 1986 Chernobyl catastrophe after 20 years by linking geographic variation in radioactive fallout to respondents of a nationally representative survey in Ukraine according to their place of residence in 1986. The psychological effects of this nuclear disaster are large and persistent. More affected individuals exhibit poorer subjective well-being, higher depression rates and lower subjective survival probabilities; they rely more on governmental transfers as source of subsistence. We estimate the aggregate annual welfare loss at 6 8% of Ukraine's GDP highlighting previously ignored externalities of large-scale catastrophes.
Keywords: I31; I18; D62; Q51; H12; 330; Chernobyl; nuclear catastrophe; externality; subjective well-being; mental health; depression; transfer dependency; welfare loss; natural experiment